Dari Warga untuk Warga: Penyerahan Bantuan Donasi kepada Penyintas Banjir Bandang di Kecamatan Pante Bidari, Aceh Timur - Ayu Rahmi; Agus Muliaman; Fakhrah Fakhrah; Muliana Muliana; Ucia Mahya Dewi (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
Flash floods are a hydrometeorological disaster that frequently strikes Indonesia, including East Aceh. Their impacts include not only physical damage but also social and economic disruption to residents. This article describes a community service activity involving the distribution of community donations to flash flood survivors in Pante Bidari District. Using a descriptive qualitative approach, this article analyzes the process of collecting, managing, and distributing aid and links it to theoretical findings in the scientific literature on disaster management, social solidarity, and community resilience. The literature review indicates that local community involvement significantly influences the effectiveness of disaster management (Hariyal & Anhar, 2015); (Faiz, 2025) The results of this activity indicate that community-based aid distribution can accelerate the fulfillment of basic needs, strengthen social networks, and increase the social resilience of affected communities. Thus, this activity confirms that strengthening solidarity among residents is a crucial component in disaster emergency response. Community-based aid distribution not only ensures targeted assistance but also fosters a spirit of mutual cooperation that strengthens long-term social resilience.